Food Safety at Tailgating - Soohyoun Ahn; Amarat H. Simonne; Keith R. Schneider (EDIS)
While tailgating can be a great fun for family and friends, you need to make plans and take on-site precautions to keep your food safe during these events. Since refrigerators and running water are not always available for the events, you should familiarize yourself with the safe food handling practices for these outdoor events and plan ahead so you will be prepared with enough coolers/ice and all the tools you need to keep and cook your food safely. This 3-page fact sheet provides information on safe food practices for tailgating and other outdoor sporting events. Written by Soohyoun Ahn, Amarat H. Simonne, and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition, October 2014.